Workplace Incivility: A Research on Veterinarians - Rüzgar, Nilüfer (IGI Global, 2024)
In the globalizing world, organizations are in fierce competition, the use of technology is increasing and therefore it is difficult for some employees to adapt to this, in addition to the increasing population which resulting in difficulties in finding a job and the desire not to lose the current job. In this sense, employees who are under stress can consciously or unconsciously can behave rude to each other. In this context, the aim of this study is to investigate the perceptions of workplace incivility of veterinarians working in private clinics. Within the scope of the research, a survey consisting of the Workplace Incivility Scale and demographic questions, developed by Cortina, Magley, Williams and Langhout (2001) and adapted into Turkish by Gök, Karatuna and Başol (2019), was prepared and delivered to the participants. According to the findings, there is a statistically significant difference (p < 0.05) between gender characteristics and age characteristics and workplace incivility. © 2025 by IGI Global Scientific Publishing. All rights reserved.
Keywords: current; Cortina; Statistically significant difference; Turkishs; Williams